A Comparative Review of Chitinase Enzymes from Microbial and Mammalian Origins and Their Roles in Health Applications - Prima Novitasari; Maria Ulfa Nur Hidayanti; Maria Estela Karolina; Amalia An Nidha (Universitas Labuhanbatu, 2025)
Background: Chitinase is an enzyme crucial in chitin biodegradation, breaking the 1,4-N-α-acetyl-D-glucosamine bonds of its monomers. It is produced by a wide range of organisms, from microorganisms such as bacteria and fungi to macroorganisms including humans. Chitinases have been widely studied for applications in biological control, environmental management, and medical fields, including immune modulation and infection therapy. However, there is still a research gap due to the limited number of systematic comparative studies examining the structural, genetic, and functional differences among chitinases from various biological sources. This limitation hinders optimal and targeted use of chitinases in enzyme-based technologies, particularly for medical applications. Therefore, comprehensive studies are needed not only to describe chitinases by their sources but also to evaluate their practical potential and innovative opportunities for human health. Methods: This study uses a narrative literature review approach. Articles were collected, screened, and systematically organized according to their scope, focusing on chitinase sources, mechanisms of action, and applications in healthcare. Results: The analysis shows fundamental differences in domain structure, gene expression, and catalytic mechanisms of chitinases from bacteria, fungi, and humans. Bacterial chitinases exhibit environmental stability and serve as infection biomarkers, fungal chitinases excel in immunotherapy and bioactive compound production, and human chitinases, though less explored, show potential in precision diagnostics and inflammatory therapy. Conclusions: This cross-domain comparison maps structural and functional characteristics and opens opportunities for integrating cross-species enzyme functions for innovative enzyme-based biopharmaceuticals and precision therapies addressing modern pathogens